Conference report: The First Argentine Symposium of Medical Science Applied to Tennis (1999)
Summary of the highly succesful symposium on tennis medicine on 25 June 1999 which was sponsored by the Argentine Tennis Association and which attracted more than 350 sport-related professionals for a lively scientific debate. Physicians, physical trainers, athletic trainers and psychologists travelled from all over Argentina, as well as from Bolivia and Uruguay, to exchange ideas with international experts in sports medicine. Dr. Múscolo, an internationally recognized orthopaedic surgeon and researcher, opened the symposium with a presentation entitled "Misdiagnosis of knee tumors simulating intra-articular sports-relate lesions". Dr.Khoury presented some of the latest findings relating to shoulder instability, while DR. Maquirriain addressed the meeting on the endoscopic treatment of chronic Achilles tendinopathies. Other interesting presentations were delivered by Dr. Miguel Ayerza, on sports activities after arthroplasty, Dr. Isabel Díaz on the metabolic demands of tennis, and by Dr. Walter Mira on muscular oxidative stress. Athletic trainer Hernán Puerta presented an anthropometric profile of competitive Argentine tennis players, while Roberto Andersen, a pioneer of Argentine tennis journalism, summarized the history and evolution of tennis in Argentina. Prof. Rostagno gave the closing address. The Argentine Tennis Association is working hard to improve sports science and player development in Argentina. Its next goal is to develop a network of physicians specialized in tennis, to ensure high quality sports medical care for all junior tennis players in the country.